Directives in Japanese: Evidence from signs. Issue 1 (March 2015) - MORROW, PHILLIP R.; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT This study deals with the description and analysis of directives in Japanese. Data is drawn from public signs and announcements. The study is organized around two issues: the linguistic forms associated with directives and the use of graphics. Regarding linguistic forms, there was found to be a strong tendency for directives to be framed as requests. Imperative forms were avoided and other strong forms used infrequently. Although the directives were impersonal, being directed at a general audience, there was a clear concern with mitigating the face‐threat of directives. This was evident in the preference for framing directives as requests, in the avoidance of imperative forms, and in the prefacing of directives by explanations or statements of purpose. One distinctive characteristic was the use of the ‐mashoo ('let's') form for directives. This use can be attributed to politeness concerns and a sense of empathy. Graphics, usually in the forms of caricatures and cartoon‐like characters, were often used on signs with directives. The association of graphics with directives is related to the popularity of anime and manga in Japanese culture, where they are used not only for entertainment, but instruction.